Can Global Value Chains Effectively Serve Regional Economic Development in Asia? - Hans-Peter Brunner (Asian Development Bank (ADB), 2013)
Regional economic integration through logistics, information network and connectivity improvement can increase the 'virtual size' of an economy as trade with neighboring countries increases. This leads to substantial benefits from scale, network, coordination and agglomeration economies. As is shown, especially in small economies and LDCs, regional economic integration induces the necessary rebalancing needed for integration of the regional portions of Global Value Chains (GVCs) to the global portions of GVCs. This paper demonstrates this with South Asian case studies in GVC development and with the related mapping methodology. This methodology traces a product through an entire channel across a region, from the point of product conception to the point of consumption. As an appropriate set of investment and policy measures is undertaken across a region, it can as we show in the paper, lead to a substantially ‗rebalanced` way of income growth.
hdl:11540/2327
Keywords: C15; F12; F15; O18; R12; 330; Rebalancing; spatial distribution of growth; regional economic integration; South Asia; value chains; Wirtschaftswachstum; Wirtschaftliche Konvergenz; Regionale Wirtschaftsintegration; Wertschöpfung; Asien